FROM "STREET ARAB" TO SCHOLAR: NEGOTIATING THE STATUS OF THE ORPHAN IN LATE VICTORIAN CANADIAN LITERATURE - Donny Syofyan (Krinok:Jurnal Linguistik Budaya, 2026)
This article examines the status negotiation of the orphan in late Victorian Canadian literature through a postcolonial and settler-colonial lens. The primary objective is to analyze the transformation of the protagonist, Anne Shirley, from a marginalized Street Arab to an enfranchised Scholar, illustrating how this trajectory mirrors the consolidation of the British-Canadian settler state.  The methodology employs a qualitative literary analysis of Lucy Maud Montgomery’s Anne of Green Gables (1908), utilizing close-reading techniques and coding for themes such as linguistic re-colonization, domestic discipline, and academic meritocracy. The study specifically maps the racialized and classed anxieties of the era by tracing the shift from Anne’s initial classification as a manual labor unit to her recognition as an intellectual vanguard. Main outcomes and results reveal that settler belonging is achieved through the systematic erasure of the original inhabitants of Prince Edward Island. Anne’s imagination serves as a colonial tool to rename the landscape and impose Eurocentric romantic ideals, while education functions as a primary mechanism for individual and professional recolonization. The conclusions indicate that the orphan heroine’s success is an affirmation of the settler’s radical underlying title to the land. Ultimately, the study demonstrates that achieving domestic and social belonging in Avonlea is contingent upon mastering the imperial canon and adopting a specific British-Protestant social sensibility.